Meningkatkan hasil belajar ipa melalui metode bernyanyi lagu pembelajaran bagi siswa kelas V SD Jolosutro - Kristina kristina; Netty Fatmawati; Elisabet Novena; Sunaryati Sunaryati (Universitas Muhammadiyah Magelang, 2022)
Education in primary schools plays a role in efforts to produce responsible youth. Many parties pay great attention to that basic education is a bridge for efforts to increase the development of the nation's human resources. There are several methods that can be applied in learning to support the improvement of human resources. One method that is considered effective and efficient is applied in science learning, namely songs. Songs make learning fun, and make it easier for students to accept the material presented by the teacher. This study will observe the use of song media in improving student learning outcomes. The methods used are (1) planning, (2) action, 3) observation, (4) reflection or evaluation of fifth grade students in science subjects. The results of the observation before the action was taken. As many as 10 students (41.67%) had reached the KKM, while 14 students (58.33%) had not yet reached the KKM. After observing meetings 1 and 2 there are students whose learning activities get very good criteria at meetings 1 and 2 are 1 child with a percentage of 4% each, while children who get good criteria are 6 students (25%) and have increased to 7 students (29%). The criteria is sufficient there are 10 students (42%) and decreased to 9 students (38%). The criteria for less did not change the data at meetings 1 and 2 with a total of 7 students (29%). Evaluation of students in meeting 1 who got a minimum score of 70 there were only 11 students with a percentage of 45.83%, while at meeting 2 there were 13 students who achieved the minimum completeness criteria with a percentage of 54.17%, resulting in an increase in the passing rate.